METHODS FOR RHEOLOGICAL ASSESSMENT OF DRILLING FLUIDS - Filipiev H. S. (НТУ «ДП», 2024)
During the drilling of oil and gas wells, drilling fluids perform a multitude of critical functions, including the removal of cuttings, cooling the drilling tool, stabilizing the wellbore, and creating hydrostatic pressure to prevent formation fluid ingress. The rheological properties of these fluids, which describe their flow behavior and resistance to shear forces, are essential to maintaining well control and the efficiency of drilling operations.
Keywords: during; drilling